Outcomes of structured teaching for children on the autism spectrum: does the research evidence neglect the bigger picture?. Issue 2 (23rd October 2013) - Howley, Marie
<x xml:space="preserve">Abstract</x> The adoption of 'structured teaching' is evident in educational settings worldwide and has fast become one of the key 'tools' in autism education. As calls for evidence‐based practice have increased, research evidence has grown to interrogate the effectiveness of structured teaching components. Previous systematic literature reviews of the research evidence suggest that structured teaching has positive effects upon problem behaviours and also increases engagement and independent task organisation. This literature review builds upon previous reviews in order to explore the effects of structured teaching upon behaviour and learning, asking what the research evidence actually measures in relation to these two concepts. Gaps in the research evidence are identified, and discussion focuses upon the need for research which investigates the role of structured teaching components in meaningful learning, the need for greater attention to evaluate social validity of the approach which takes into account those who implement and indeed those who receive the intervention and finally the need for research to analyse the effects of structured teaching upon alternative outcomes of 'well‐being' and 'quality of life'.